A STUDY ON THE CONTRIBUTION OF FOUNDING BELT PAINTERS IN TURKISH PICTURE - EBİRİ, Gülsün (Atlas Journal, 2021)
The Westernization process, which started in the political and social environment of the 18th century Ottoman state, has still been reflected in art and the developments in painting are started in the process. In this process of historical, the art education was reflected in the economic and cultural conditions of the period in the education system. Picture art has also developed in this process by developing with different styluments. TURKISH PICTURE ART has continued to the present with the adoption of the new world view accelerated in the 18th century by gaining a western understanding of social and cultural changes in the 1920th century. With the contribution of the sultans supporting the westernization movements in the 19th century, the art has developed the art of painting and to be sent to France for the study of the students in Turkish painting art. In the early periods, the study of Turkish painters to Europe has contributed to the formation of contemporary Turkish painting art. The founding belt paints in Turkish picture were pioneers in Turkish picture art and have taken important steps in the formation of painting. With this study, Şeker Ahmet Ali Paşa, Süleyman Seyyid Bey, Osman Hamdi Bey, Halil Paşa and Şehzade Abdülmecit Efendi’s education in Europe and the Mihri (Rasim)Müşfik Hanım and Müfide Kadri Hanım’s Contributions on painting art will be tried to be explained.